Spectrophotometric Determination of Protein with DBC-Chlorophosphonazo - Wang, Qing-Shuang; Zhai, Qing-Zhou; Luo, Jia (Asian Journal of Chemistry, 2013)
A new spectrophotometric method for the determination of protein has been developed using the property that bovine serum albumin and DBC-chlorophosphonazo form a compound. The maximum absorption wavelength of the compound is 606 nm. Beer's law is obeyed over the range of 25-250 μg/mL of bovine serum albumin contents. The detection limit of this method is 9.52 μg/mL. Protein content in human serum has been successfully determined.